Unlocking the Potential of Liberica Coffee for Coffee Tourism in Poncokusumo, East Java from Panelist Perceptual - Wafaretta, Erona; Tri Ananda, Oriny (Journal of Coffee and Sustainability, 2025)
Indonesian coffee discoveries are increasingly focusing on the optimal utilization of under-explored species such as Coffea liberica, which can be diversified into market and tourism opportunities. This study investigates the perception of expert panelists on the flavor, post-harvest practices, and tourism potential of liberica coffee cultivated in Poncokusumo. A structured Likert-scale questionnaire was administered to nine panelists, and data were analyzed using classical assumption tests and multiple linear regression. Results indicate that panelists acknowledged the distinctiveness and acceptability of liberica coffee's flavor profile, with sensory attributes such as body, balance, and sweetness significantly influencing perception (R² = 0.489). Cultivation and roasting were considered highly adaptable, with balance and coffee accession types contributing to the perception of liberica coffee’s post-harvest process (R² = 0.274). Furthermore, sensory elements such as aftertaste, aroma, body, and total score played a significant role in shaping panelists’ enthusiasm toward coffee tourism (R² = 0.576). The study highlights that sensory preferences for balance, sweetness, and light body can guide the market positioning of liberica coffee while enhancing visitor experience and supporting identity-based coffee tourism development in Poncokusumo. By linking sensory quality with experiential tourism design, C. liberica can become a niche product for sustainable rural development.